Selective editing of a peptide skeleton via C–N bond formation at N-terminal aliphatic side chains. Issue 48 (30th November 2022) - Han, Yujie; Shi, Junjie; Li, Songrong; Dan, Tingting; Yang, Wenwen; Yang, Mingyu
Abstract : We have developed a visible light-promoted selective editing of a peptide skeleton via C–N bond formation at N-terminal aliphatic side chains. A proline skeleton was constructed in peptides under such transition metal free conditions. Abstract : The applications of peptides and peptidomimetics have been demonstrated in the fields of therapeutics, diagnostics, and chemical biology. Strategies for the direct late-stage modification of peptides and peptidomimetics are highly desirable in modern drug discovery. Transition-metal-catalyzed C–H functionalization is emerging as a powerful strategy for late-stage peptide modification that is able to construct functional groups or increase skeletal diversity. However, the installation of directing groups is necessary to control the site selectivity. In this work, we describe a transition metal-free strategy for late-stage peptide modification. In this strategy, a linear aliphatic side chain at the peptide N-terminus is cyclized to deliver a proline skeleton via site-selective δ-C(sp 3 )–H functionalization under visible light. Natural and unnatural amino acids are demonstrated as suitable substrates with the transformations proceeding with excellent regio- and stereo-selectivity.